1985
DOI: 10.1073/pnas.82.11.3761
|View full text |Cite
|
Sign up to set email alerts
|

Differential amplification, assembly, and relocation of multiple DNA sequences in human neuroblastomas and neuroblastoma cell lines.

Abstract: DNA amplification, manifested by homogeneously staining regions in chromosomes and by extrachromosomal, double minute bodies, is characteristic of many neuroblastoma cell lines. Sequences recruited from a specific domain on the short arm of chromosome 2 (2p) are amplified in advanced-stage primary neuroblastomas, whereas sequences from distinctly different regions of 2p are amplified in the neuroblastoma cell line IMR-32. Five different DNA segments, which include the oncogene N-myc, three other fragments deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
2

Year Published

1988
1988
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 28 publications
(44 reference statements)
4
55
2
Order By: Relevance
“…Our studies with PFG analysis provided information on the long-range organization of amplified units: DNA rearrangements had occurred relatively close to the Nmyc gene, however amplification units were much longer and homogeneous. Based on our observations and the data of Shiloh et al [23], the connection of several DNA fragments might be necessary in ~ some cases for amplification of DNA fragments. Such rearrangements should have occurred before, not during amplification.…”
Section: Heterogeneous Rearrangements and Homogeneous Amplification Asupporting
confidence: 67%
See 1 more Smart Citation
“…Our studies with PFG analysis provided information on the long-range organization of amplified units: DNA rearrangements had occurred relatively close to the Nmyc gene, however amplification units were much longer and homogeneous. Based on our observations and the data of Shiloh et al [23], the connection of several DNA fragments might be necessary in ~ some cases for amplification of DNA fragments. Such rearrangements should have occurred before, not during amplification.…”
Section: Heterogeneous Rearrangements and Homogeneous Amplification Asupporting
confidence: 67%
“…Shiloh et al [23] demonstrated that at least three DNA fragments derived from different chromosome loci were simultaneously amplified in HSR of IMR-32. Since they employed in situ hybridization, it was unclear whether these DNA fragments were connected to each other in the same amplification unit.…”
Section: Heterogeneous Rearrangements and Homogeneous Amplification Amentioning
confidence: 99%
“…Thus, N-myc is considered the main factor in driving the selective pressure for ampliÂŽcation. However, a number of investigators have found that rearrangements are common in the neuroblastoma amplicon (Akiyama and Nishi, 1991;Amler and Schwab, 1992;Shiloh et al, 1986), suggesting that there may be additional selective pressure for the inclusion or exclusion of other genes. It is also noteworthy that some studies have shown that not all tumors with N-myc ampliÂŽcation are associated with a bad prognosis; for example, 50% of stage II tumors with N-myc ampliÂŽcation have a good outcome De Bernardi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that there are usually large differences between the amplified units in independently selected highly amplified mutants (2,5,12,34,36). On the contrary, the highly amplified units within each line are relatively homogeneous.…”
Section: Discussionmentioning
confidence: 97%
“…In most cases, the results point to remarkable differences between the sequences coamplified in independent highly amplified mutants: the amplified units include a region comprising the selected gene and sequences immediately surrounding it in the wild-type line, but also include sequences which are amplified uniquely in each cell line (2,5,12,34,36,43). Thus, during the amplification process, pieces of DNA from different parts of the genome are joined by recombination to form novel structures and novel joints (new restriction fragments).…”
mentioning
confidence: 99%